1980
DOI: 10.1111/j.1365-2311.1980.tb01161.x
|View full text |Cite
|
Sign up to set email alerts
|

The distribution in time and space of parasitism in Epinotia tedella (CI.) (Lepidoptera: Tortricidae)

Abstract: 1 . The temporal and spatial distribution of parasitism in Epinotia tedella was investigated within two spruce stands.2. Most eggs were laid by the host female early in the season. The parasitoid, Pimploptenrs dubius, was subjected to a temporal stress, and it also exhibited a greater oviposition rate early in its life. The temporal distribution of attack frequencies by P.dubius and Apanteles tedellae showed a good adaptation to the phenology of the host.3. The spatial distribution of flight activity indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…6 and 7). Recent detailed population studies on other herbivorous insects have revealed the effects of such seasonal variability ("temporal window") of arthropod predators or parasitoids on the population dynamics of the prey or host (e.g., Miinster-Swendsen 1980, Myers 1981, Clancy and Price 1986, Jones et al 1987. Besides arthropod predation, there were two seasonally specific factors affecting egg and larval survival in later cohorts: heat stress at the egg stage and host deterioration at the larval stage.…”
Section: Variation In Cohort Lifetime Fitnessmentioning
confidence: 99%
“…6 and 7). Recent detailed population studies on other herbivorous insects have revealed the effects of such seasonal variability ("temporal window") of arthropod predators or parasitoids on the population dynamics of the prey or host (e.g., Miinster-Swendsen 1980, Myers 1981, Clancy and Price 1986, Jones et al 1987. Besides arthropod predation, there were two seasonally specific factors affecting egg and larval survival in later cohorts: heat stress at the egg stage and host deterioration at the larval stage.…”
Section: Variation In Cohort Lifetime Fitnessmentioning
confidence: 99%
“…Both types of responses are important to the population dynamics of the host, but the two should not be combined into one catch-all category of density dependence. The literature review contains many examples of studies that consider only spatial responses (e.g., Eikenbary and Fox 1968, Miinster-Swendsen 1980, Gargiullo and Berisford 1981, Lashomb and Steinhauer 1982 and others that consider only temporal responses (e.g., Harcourt 1971, Ryan 1983, Sunose 1985. The objective of the literature review was to identify biological features of density dependence; pooling two different forms of density dependence could obscure biological features of either form.…”
Section: Temporal Vs Spatialmentioning
confidence: 99%
“…Other confounding factors in the cited studies include host density being related to tree crown height (Eikenbary and Fox 1968, Miinster-Swendsen 1980, Lashomb and Steinhauer 1982, altitude (Randalll982), host species (Burleigh 1972), and seasonal development of the host plant (Vorley and Wratten 1985). When host density is correlated with such factors, any parasitism trends could be due either to host density or to the environmental factor.…”
Section: Confounding Factorsmentioning
confidence: 99%
“…The purpose of the paper was to show how my approach to population analysis (Berryman 1990, 1999, 2001) could be used to detect the causes of population cycles in his data on the spruce needle‐miner, Epinotia tedella (Cl.) (Münster‐Swendsen 1979, 1982, 1985). I should point out here that, at the time we first met, Mikael was not too impressed with my approach, being a proponent of the life table–key factor approach (Varley et al 1975).…”
mentioning
confidence: 99%